Masalah Perbatasan dan Intensifitas Konflik Di Afrika - Hennida, Citra (Global and Policy Journal of International Relations, 2014)
ABSTRACTThe intensity of the civil war in the nations of africa is high. Rebel movements become difficult to overcome, one of the problem because the involvement of countries outside the state of that which is undergoing a conflict.This shows the lack of parts of the border in Africa. A question proposed is what causes parts of the border in african countries weak? Then what contribution to the intensity of the civil war in african countries? This article argue that the border area in african countries is weak caused by a legacy of colonial who divide an area of the state with the scattered ethnic groups, obscures the reality economic reasons related to natural resources which its existence cross-border countries, and the lack of a political commitment to strengthen national boundaries. Three it is indicated that there is actually no borders of a territory in africa and control over parts of the border is ineffective.Keywords: border menagement, civil conflict, Africa.DOI:https://doi.org/10.33005/jgp.v2i01.1978